2018
DOI: 10.3390/su10020558
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sector Social Partnerships for Social Change: The Roles of Non-Governmental Organizations

Abstract: Abstract:Complex social and environmental issues call for broader collaboration across different sectors so as to instigate transformative social change. While previous scholars have emphasized the role of non-governmental organizations (NGOs) in facilitating social change, they have not provided a nuanced assessment of NGOs' different roles. We use the Poverty and Employment Precarity in Southern Ontario (PEPSO) research partnership as a study case and explore NGO partners' different roles in a large cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…A range of CSPfS have emerged to address the evolving nature of social problems [44], the extent [45,46] and complexity of social and environmental issues [46,47], and the failure of actions from isolated governments [6][7][8] and social sector organizations [8]. In fact, CSPfS have been promoted as "social problem-solving mechanism among organizations" [48] (p. 79).…”
Section: Cross-sector Partnerships For Sustainability (Cspfs)mentioning
confidence: 99%
See 2 more Smart Citations
“…A range of CSPfS have emerged to address the evolving nature of social problems [44], the extent [45,46] and complexity of social and environmental issues [46,47], and the failure of actions from isolated governments [6][7][8] and social sector organizations [8]. In fact, CSPfS have been promoted as "social problem-solving mechanism among organizations" [48] (p. 79).…”
Section: Cross-sector Partnerships For Sustainability (Cspfs)mentioning
confidence: 99%
“…On one side, governments find an alternative way to produce public goods-a typically governmental prerogative-by involving firms [57] and social sector organizations [58]. On other side, firms-especially large corporations-find a way to generate a "long-term competitive advantage" [43] (p.2), while social sector organizations gain ways to finance social issues [46]. In fact, Kolk et al [59] found that CSPfS produced effects at three different levels: macro level, meso level, and micro level.…”
Section: Cross-sector Partnerships For Sustainability (Cspfs)mentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the role of NPOs has changed, and increasingly, these organizations are initiating CSPs together with business actors, in which they can play a variety of important roles, such as convener or facilitator [46]. Working in CSPs implies that businesses have to develop a broader perspective of a more inclusive supply chain that also includes competitors and 'non-traditional' supply chain actors such as NPOs [40], inevitably leading to multi-actor CSPs and 'cross-level dynamics' among its stakeholders [16].…”
Section: Npos' Shifting Role(s) In Stimulating Sustainability In Globmentioning
confidence: 99%
“…In this sense, the Cross-Sector Social Partnerships, and in particular, the collaborative relationships between corporations and non-profit organizations (NPOs) in the development of their Corporate Social Responsibility (CSR) policies, have become widely accepted by both types of organizations to work together [3][4][5] in order to confront difficult problems [6,7]. An example of a collaboration agreement created to deal with this type of problem was the social cooperation between the business Unilever and World Wildlife Fund (WWF), aimed at the creation of an ecologically sensitive brand with the objective of helping guarantee the sustainability and integrity of the marine ecosystem.…”
Section: Introductionmentioning
confidence: 99%